Sertifikasi Halal bagi Produk UMKM di Desa Nyurlembang, Kabupaten Lombok Barat - Nabila, Riska; Syukron Jayadi; Rusman Hadi, Muhammad; Fitrianingsih, Rahmawati; Sukron Haekal Ramdani, Akhmad (ISAS (Indonesian Society of Applied Science), 2023)
Most of the Micro, Small, and Medium Enterprises (MSMEs) in West Nusa Tenggara are engaged in the culinary (food) industry, with one such enterprise located in Nyurlembang Village, Narmada District, West Lombok Regency. Generally, the food products produced by MSMEs in Nyurlembang Village lack halal certification, which can lead to consumer hesitancy, especially among Muslims. Therefore, conducting socialization activities related to halal certification for MSMEs in Nyurlembang Village is of paramount importance. The purpose of these socialization activities is to educate and enhance the understanding of MSME operators regarding the significance of halal product certification. The implementation of this socialization employs lecture-style sessions and direct discussions. The socialization activities consist of three stages: preparation, execution, and evaluation. Overall, community service activities through halal certification socialization were successful, as evidenced by the active discussions held between business operators and the resource persons delivering the material. However, a challenge encountered during the implementation of this socialization was the timing, which was not optimal